Effect of feeding at different levels of single or twin pregnant konya merino ewes on the live weights, body condition of ewes and growth of lambs - Ahmet Hamdi Aktaş; Mehmet Gürkan; Hüseyin Erdem (Eurasian Journal of Veterinary Sciences)
Aim: The aim of the present study was to examine the effect of feeding with ratios containing different nutrient levels of single or twin pregnant ewes during the last gestation on the live weights (LW), body conditions of Konya Merino ewes and growth and survival rate of lambs until weaning. Materials and Methods: For this aim, first, 120 ewes were synchronized with hormone at mating season (September) and mated. After pregnancy statuses of ewes were determined via ultrasound imaging, 54 single and 54 twin pregnant ewes were separated 6 subgroups (3 singles, 3 twins). After, this ewes were fed until birth with 6 different rations (containing different nutrients levels) according to daily nutrient requirement of NRC (100%), below (80%) or above (120%) as groups during the last 6 weeks of pregnancy. Results: In the study, the differences between live weights and body condition scores of ewes before birth were significant (P<0.05). When examined the live weights of lambs born from ewes fed different level during the last pregnancy, differences between the single and twin groups were significant (P<0.05). But, when singles and twins were analysed separately, differences between the groups were not (P>0.05) significant. Also, survival rates of lambs until weaning insignificant (P>0.05). Conclusion: As a result, it can be said that feeding of Konya Merino ewes during the last 6 weeks of pregnancy with ration about 80% of the level of daily nutrient requirements recommended by NRC may be sufficient for optimal growth of lambs until weaning.